Two sides of the coin: coagulation and inflammation in deep vein thrombosis – a prospective study on D-dimer and SIRI - Kahraman, Ercan; Cetin, Sirin; Cetin, Meryem; Ulgen, Ayse (Frontiers in Medicine, 2025)
BackgroundDeep vein thrombosis (DVT) is a major cause of morbidity and mortality, including pulmonary embolism and post-thrombotic syndrome. This study aimed to assess the effectiveness of inflammatory indices, derived from routine laboratory parameters, in predicting DVT.MethodIn this prospectively designed study, patients diagnosed with DVT through Doppler ultrasound at a tertiary healthcare center between December 2024 and February 2025, along with a control group confirmed to be DVT-free by Doppler ultrasound, were analyzed. Blood markers such as D-dimer, CRP, IL-6, and inflammatory indices (SIRI, MHR, PLR) were compared between groups. Statistical tests included chi-square, t-tests, logistic regression, and ROC curve analysis. Diagnostic performance was measured using odds ratios (ORs) with 95% confidence intervals (CIs).ResultInflammatory markers (SIRI, MHR, D-dimer, CRP, IL-6) were significantly elevated in DVT cases. SIRI demonstrated high diagnostic accuracy (AUC: 0.934) with a threshold of 0.97. Combined SIRI and D-dimer analyses yielded 93% positive and 100% negative predictive accuracy.ConclusionThis study demonstrated that inflammatory markers, particularly SIRI, were elevated in patients with deep vein thrombosis (DVT) and carried high predictive value in this patient group. The combined use of SIRI and D-dimer provided high diagnostic accuracy for DVT. SIRI, a low-cost index calculable through routine blood tests, was shown to be more effective than other inflammatory markers in predicting DVT. Additionally, the combination of SIRI and D-dimer yielded high positive and negative predictive values for DVT diagnosis.